2015
DOI: 10.4238/2015.march.31.1
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin resistance among multi-resistant MRSA clinical isolates from Chennai, India, and their molecular characterization

Abstract: ABSTRACT. High-level methicillin-resistant Staphylococcus aureus (MRSA) isolates show rapid evolution of rifampicin resistance, forcing reliance upon expensive and often inferior antibiotics to manage these infections. Accordingly, this study was conducted to: 1) evaluate the level of multidrug resistance among hospital-associated MRSA isolates from Chennai, India; 2) determine their rifampicin resistance and molecular characterization; and 3) analyze the identified rpoB gene mutations for predominant high-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…A study conducted by Umadevi et al, reported that Amikacin, Piperacillin/tazobactum and Imipenem were sensitive against Gram negative bacteria [24]. This present scenario distinguished from a study in Chennai that they reported E.Coli showed 100% sensitivity to Imipenem and Meropenem and they are resistant against Gentamycin [25]. Our study reported that E.Coli exhibited (83%) sensitivity to Clotimaxazole, (75%) to Meropenem and (33%) to Imipenem.…”
Section: Discussioncontrasting
confidence: 59%
“…A study conducted by Umadevi et al, reported that Amikacin, Piperacillin/tazobactum and Imipenem were sensitive against Gram negative bacteria [24]. This present scenario distinguished from a study in Chennai that they reported E.Coli showed 100% sensitivity to Imipenem and Meropenem and they are resistant against Gentamycin [25]. Our study reported that E.Coli exhibited (83%) sensitivity to Clotimaxazole, (75%) to Meropenem and (33%) to Imipenem.…”
Section: Discussioncontrasting
confidence: 59%
“…Figure 2 and the overall MAR index of tested strains was 0.48±0.12 (Figure 3). The tested MRSA strains had very high MAR index value since MAR index value just≥0.2, is considered high 40 and might be originated from environments with misuse of antibiotics where resistance developed and spread, 43 rather than harboring both mecA & icaA genes (Figure 4). All tested MRSA strains showed positive congo red testing concluding that these tested strains were biofilm producing MRSA pheno as well as genotypically.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with similar sample populations reported increased resistance rates of MRSA isolates to erythromycin, tetracycline [5,25,26] . However, resistance to rifampicin and kanamycin is observed in clinical MRSA isolates mostly isolated from hospitalized patients [27,28] . The reason may be the excessive use of such antibiotics in our sample population because they are still easily accessible in our country.…”
Section: Discussionmentioning
confidence: 99%